Starspots and Rotation Velocities of Normal A- And Am- Stars - Trust, O; Jurua, E; Cat, P. De; Joshi, S (Stars and their Variability Observed from Space, 2020)
Using the \hump and spike" features, we computed the rotation frequencies and amplitudes. The corresponding equatorial rotational velocity (Vrot) and spot size were estimated. On _tting the auto-correlation functions of the light-curves with the appropriate model, we obtained the starspot decay-time scale. The Vrot agrees well with the projected rotational velocity (_ sin i) in the literature. Considering a single circular and black spot, we estimate its radius from the amplitude of the \spike". No evidence for a signi_cant di_erence in the average \spike" amplitude and spot radius was found for Am/Fm and normal A stars. Indeed, we derived an average value of _ 21_2 and _ 19_2 ppm for the photometric amplitude and of 1:01 _ 0:13 and 1:16 _ 0:12RE for the spot radius (where RE is the Earth radius), respectively. We do _nd a signi_cant di_erence for the average spot decay-time scale, which amounts to 3:6 _ 0:2 and 1:5 _ 0:2 days for Am/Fm and normal A stars, respectively. In general, spots on normal A stars are similar in size to those on Am/Fm stars, and both are weaker than previously estimated. The existence of the \spikes" in the frequency spectra may not be strongly dependent on the appearance of starspots on the stellar surface. In comparison with G, K and M stars, spots in normal A and Am/Fm stars are weak which may indicate the presence of a weak magnetic _eld.
Keywords: Stars: photometry; Stars: chemically peculiar; Stars: rotation; Stars: starspots